Employee Performance Factors at PT. Boston Nusantara - Joko Bagio Santoso; Akhmadi, Ali; Nafisah, Siti (Penelitian dan Pengembangan Ilmu, 2024)
Employees are valuable assets to the organization, and their efforts will help the company accomplish its mission. Companies that cannot manage and monitor their employees' performance will negatively impact the achievement of the company's goals and vision. Employee commitment supported with excellent work discipline and a high level of job satisfaction has an impact on employee performance. However, there are still employees that are uncommitted and lack strong work discipline. This study aims to investigate and identify some of the factors of employee performance at PT. Boston Nusantara, such as employee commitment, work discipline, and job satisfaction. The multiple correlation and the determination coefficient methods were employed in this study. The results showed that (1) Employee Commitment Variable had no effect on Employee Performance, (2). Employee Performance is influenced by Work Discipline Variable. (3). Employee Performance is influenced by Job Satisfaction Variable. (4). Simultaneously, Employee Performance is influenced by the variables of Employee Commitment, Work Discipline, and Job Satisfaction. The implication of this study is that the organization must develop a work environment that encourages employees to maintain persistent commitment, work discipline, and job satisfaction to create a collaborative work environment and achieve the company goals.